Complex systems engineering : theory and practice - Flumerfelt, Shannon; Schwartz, Katherine G.; Mavris, Dimitri; Briceno, Simon (Progress in astronautics and aeronautics ;, 2019)
Complex Systems Engineering: Theory and Practice represents state-of-the-art thought leadership on system complexity for aerospace and aviation, where breakthrough paradigms and strategies are sorely needed. The costs and consequences of current knowledge and practice gaps are substantial. In short, this problem is caused by several factors: the lack of human capacity to comprehend complexity without machine/autonomation interfaces, the rapid pace of changes i.